STANDARDIZATION AND VALIDATION OF QUALITATIVE REAL TIME RT-PCR FOR DETECTION OF CLASSICAL SWINE FEVER VIRUS - Chiok C., Kim Lam (2011)
A real time RT-PCR assay was standardized and validated for detection of classical swine fever virus (CSFV). Tonsil tissue and lymph nodules that were positive (n=36) and negative (n= 30) to CSFV by immunofluorescence test (IF) were selected. The viral RNA extraction, the complementary DNA (cDNA) synthesis and real time RT- PCR were performed using commercial kits. Three sets of primers were tested for amplification of a conserved region (5’UTR) of panpestivirus and 5’UTR Chinese strain and the E2 glycoprotein region (E2 PPC) against reference strains of CSFV: Alfort/187, Brescia, and a vaccine Chinese strain as positive controls, and strains of the bovine viral diarrhea virus, border disease virus and porcine rotavirus as negative controls. The 83.3 ± 12.3% (30/36) of positive simples to CSFV by IF test was positive for virus isolation and the 96.7 ± 3.3% (29/30) of negative samples to CSFV by IF was negative for virus isolation. The results of real time RT-PCR assay were determined by the analysis of cycle threshold (Ct) and temperature of melting (Tm) values between the positive and negative controls and the positive and negative to CSFV of field samples. The primer E2 of CSFV recognized all positive and negative controls. The real time RT-PCR assay detected at least 4.28 pg of RNA of CSFV Brescia strain. The validation of the real time RT-PCR was performed comparing the results of positive and negative to CVSFV by isolation test and the results of real time RT-PCR assay. The real time RT-PCR assay had a sensitivity of 96.8 ± 6%, specificity of 82.9 ± 12% and a predictive positive and negative value of 83.3 ± 12.3% and 96.7 ± 3.3% respectively. The real time RT-PCR assay has a high sensitivity and specificity for the diagnosis of CSFV.